(untitled) (Journal of Engineering, 2006)
The concept of capacity and level of service are the control points of the analysis of intersections and must be fully considered to evaluate the overall operation of the intersections. The objectives of the present study include the analysis, evaluation and improvement of the operation for AL-Motanabi square in Kut city and to present a best proposal to enhance the performance from the capacity point of view. To achieve these objectives, the estimated distribution of the traffic data in different direction that required for the traffic and geometrical analysis were gathered manually, while SIDRA traffic program is used for the requirements of traffic analysis process. It has been concluded that, two layer flyover is the best proposal to improve the operation ability of AL-Motanabi square.